2021
DOI: 10.1101/2021.01.29.21250806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pelvic Pain: what are the symptoms and predictors for surgery, endometriosis and endometriosis severity?

Abstract: BackgroundChronic pelvic pain (CPP) is a common condition which significantly impacts the quality of life and wellbeing of many women.Laparoscopy with histopathology is recommended for investigation of pelvic pain and identification of endometriosis with concurrent removal. Never-the-less, the association between endometriosis and pelvic pain is challenging, with endometriosis identified in only 30-50% of women with pain.AimsTo explore the predictors for undergoing surgery, for identifying endometriosis and en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We need to acknowledge that presently there are no symptoms, symptom cluster nor algorithm that enables us to identify if superficial peritoneal endometriosis is present 12,13 and to question the pursuit of such an algorithm when it has been shown that those with pelvic pain and no demonstrable lesions share the same characteristics 13–15 and central changes as those with the symptoms 6 . This approach risks delaying the commencement of effective management strategies for pain while we expend valuable health dollars, often at substantial out‐of‐pocket costs for our patients.…”
mentioning
confidence: 99%
“…We need to acknowledge that presently there are no symptoms, symptom cluster nor algorithm that enables us to identify if superficial peritoneal endometriosis is present 12,13 and to question the pursuit of such an algorithm when it has been shown that those with pelvic pain and no demonstrable lesions share the same characteristics 13–15 and central changes as those with the symptoms 6 . This approach risks delaying the commencement of effective management strategies for pain while we expend valuable health dollars, often at substantial out‐of‐pocket costs for our patients.…”
mentioning
confidence: 99%